ANALISIS KEGAGALAN CURRENT TRANSFORMER (CT) TIPE DUA BELITAN SEKUNDER DENGAN INTI MAGNETIK TERPISAH PADA SISTEM PROTEKSI DAN PEMBATAS DAYA - Iriandi Ilyas; Muhamad Taufan Agassy (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT Current transformers function to transform large currents into small currents used for electrical energy measurement instruments, power limitation and protection of electric power networks, current transformers have many types, the use of current transformers in actual facts such as electrical power requested by consumers to producers of electricity providers at 53 kVA to 197 kVA using a single ratio current transformer type and> 197 kVA using a secondary twisting transformer type with a separate magnetic core In this type of current transformers with different ratios have different saturation values also due to high interference current values, so they are not able to provide an accurate secondary current value according to the class and the ability of current transformers against measuring instruments, power limitation and protection of electric power networksBy analyzing the failure of these types can be a reference or reference in the use of current transformers by selecting the appropriate type, ratio and accuracy class on the electricity network